Fashion and biopower: nudity in Vanessa Beecroft Performances (ModaPalavra e-periódico, 2024)
The article presents a discussion on fashion and biopower, through the nudity present in the performances of Italian artist Vanessa Beecroft for major fashion brands between 1996 and 2003 via an integrative bibliographical review. It questions how does fashion project itself onto the body and exceed matter and dress in the contemporary world. The body occupies a central role within the countless visual representations conveyed in the media. Parameters classify and regulate bodies. Models are idealized and propagated in magazines, newspapers, on social networks, etc. Biopower is known to regulate life and this means regulating discursive practices about the body. As a result, it is understood that the body documents power relations, which constitute it within discourses that regulate it, sometimes producing transitory subjectivities, sometimes desubjectivizing the body, permeating disciplinary practices and the knowledge that shapes and standardizes it.
Keywords: fashion; nudity; Vanessa Beecroft